Pengaruh Penggunaan Media Animasi Audio-Visual Terhadap Hasil Belajar Ipa Siswa Kelas IV SD Inpres Lasepang Kabupaten Bantaeng - Sitti Zahra Amalia Faisal; Hilmi Hambali; Irmawanty Irmawanty (Journal Innovation In Education, 2023)
Sitti Zahra Amalia Faisal. 2023. The Effect of Using Audio-Visual Animation Media on Class IV Science Learning Results at SD Inpres Lasepang, Bantaeng Regency. Thesis. Department of Elementary School Teacher Education. Faculty of Teacher Training and Education. Muhammadiyah Makassar University. Supervisor I Hilmi Hambali and Supervisor II Irmawanty.This study aims to (1) To find out student learning outcomes after using audio-visual animation media in Class IV SD Inpres Lasepang, Bantaeng Regency; (2) To determine the effect of using audio-visual animation media in class IV of the Lasepang Presidential Instruction, Bantaeng Regency. This research is a quantitative research with a quasi-experimental research approach with a research design using an experimental method that also uses two groups, namely the experimental group and the control group. Then the sample is class IV with a total of 40 students. With a purposive sampling technique. Data collection techniques use descriptive statistical analysis and inferential statistical analysis. The results show that there are science learning outcomes with material on force and motion of objects. This can be seen in the average posttest score for the experimental class which reached 85.35, while the average posttest for the control class only reached 65.70. Based on hypothesis testing using the independent sample t test, the t count value = 6.231, while the t table value = 2.024. Based on the results obtained t count < t tabel (t count=6.231< t tabel=2.024. Thus Ho is rejected and H1 is accepted.